TINJAUAN YURIDIS UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN TERHADAP TINDAKAN WANPRESTASI PELAKU USAHA - Asri, Ni Kadek Sindhu; Kariyasa, I Made (Jurnal Hukum Mahasiswa, 2024)
The purpose and context of analyzing the legal aspects of consumer protection based on Law Number 8 of 1999 concerning Consumer Protection (UU No. 8/1999). This thesis suggests paying attention to the acts of default by business actors, which is an important aspect in the context of consumer protection. This juridical review will cover various aspects related to business actors' acts of default, including definitions, conditions that trigger acts of default, and their impact on consumers. This thesis will analyze how Law no. 8/1999 strengthens consumer rights in overcoming acts of business actor default, as well as how these provisions can be applied in legal practice.